Experimental Investigation of Geosynthetic-Reinforced Pile-Supported Composite Foundations under Cyclic Loading - Kaifu Liu; Yiguo Yang; Lei Wang; Jiapei Xu; Xinyu Xie (Advances in Civil Engineering)
A series of model tests were conducted in this study to investigate the deformation characteristics of geosynthetic-reinforced pile-supported (GRPS) composite foundations under cyclic loading. The effects of the applied load, the number of geogrid layers, and types of piles on the performance of the GRPS composite foundation were studied through 1g physical models of composite foundation with well-planned instrumentation. Furthermore, a numerical fitting method was used to assess the relationship between the foundation settlement and the number of load cycles. The results show that with the increase in the magnitude of cyclic load and the number of load cycles, the settlement of GRPS composite foundations and the strain of the pile and geogrid increased accordingly. Adding rigid piles and increasing the number of geogrid layers both could reduce the settlement of GRPS composite foundations, while adding rigid piles was more effective. The relationship between the foundation settlement and the number of load cycles can be expressed by an exponential regression function. The pile strain varied from place to place that the strain of the upper part of the pile was greater than that of the lower part. The geogrid showed a significant impact on the load transfer mechanism of the composite foundation as the geogrid closer to piles endured larger strain. It is critical to consider the variation of the pile strain and the geogrid strain under cyclic loading in the geotechnical practice of composite foundation. The model test results also suggest that the use of GRPS system can effectively reduce the composite foundation settlement. This paper can provide useful references for developing the theoretical framework and design guides for GRPS composite foundations under cyclic loading.